Penerapan Mediasi dalam Penyelesaian Sengketa Wanprestasi Hutang Piutang di Pengadilan Negeri Gianyar - Putri Anggun Puspasari; Ni Luh Made Mahendrawati; Desak Gede Dwi Arini (Warmadewa Press, 2021)
Mediation is an alternative form of dispute resolution. Mediation has grown and developed, running fast, the desire of humans or the community to resolve disputes quickly, and satisfying both parties to the dispute, According to PERMA No. 1 of 2016 concerning Procedure for Mediation in the Court determining that Mediation is a way to settle disputes peacefully, quickly, right, and effective, can open wider access to the parties to the dispute to obtain a settlement of the case, and get a sense of justice. Accounts payable is an agreement that creates rights and obligations between creditors and debtors who are reciprocal. Accounts payable is regulated in Chapter Thirteenth of the Third Book of the Civil Code, in Article 1754 of the Civil Code. The problem is how is the application of mediation in resolving disputes over debt defaults in the Gianyar District Court? And what are the factors that influence the success of mediation in the Gianyar District Court? The research used is empirical legal research, which is looking at society in the real sense. And the problem approach used is the approach of cases in the Gianyar District Court. The conclusion obtained from this study is that the application of mediation in the Gianyar District Court is in accordance with Supreme Court Regulation No. 1 of 2016, and the factors that hinder the mediation process in the Gianyar District Court, namely both litigants do not come in the mediation process so the mediation process failed.